Swiss Cheese et allii, some of the first neurodegenerative mutants isolated in Drosophila - Kretzschmar, Doris (2009)
Drosophila has only recently become a model organism to study progressive neurodegeneration, mainly using transgenic flies expressing human disease genes. However, classical forward genetics isolating and characterizing fly mutants that show characteristic features of progressive neurodegeneration can also provide a useful tool to get insights into the mechanisms of neurodegeneration. Interestingly, the first such mutants have been already isolated in the 1970s, and this review focuses on the description of four such mutants originally isolated by Martin Heisenberg.